Long-term outcome of 25 children and adolescents with severe aplastic anemia treated with antithymocyte globulin - de-Medeiros,C.R. (2000)
Severe aplastic anemia (SAA) is probably an immune-mediated disorder, and immunosuppressive therapy is recommended for patients with no available donor for bone marrow transplant. Between October 1984 and November 1987, 25 consecutive children and adolescents with SAA with no HLA-compatible marrow donor received equine antithymocyte globulin (ATG) (15 mg kg-1 day-1) for 10 days. The patients were evaluated 6 weeks, 6 months, and 12 months after starting ATG treatment. Thereafter, patients were evaluated yearly until July 1998. Median age was 10 years (range, 1.5-20 years), granulocyte counts on referral ranged from 0.032 to 1.4 x 10(9)/l (median 0.256 x 10(9)/l), and 12 patients had granulocyte counts <0.2 x 10(9)/l. At a median follow-up of 9.6 years (range, 8.6-11.8 years), 10 patients (40%) remained alive with good marrow function. No morphologic evidence of hematological clonal disorders has been observed, although two patients probably have acquired clonal chromosomal abnormalities (trisomy 8 and del(6)q21, respectively). Responses to ATG were observed between 6 weeks and 6 months from the start of treatment in 60% of evaluable patients. The response rate was not different in patients whose granulocyte count at diagnosis was <0.2 x 10(9)/l, or in those who were <10 years of age. This study supports the view that, when compared with supportive measures, ATG is an effective treatment for children or adolescents with SAA. Although these results are inferior to those reported for marrow transplantation or more intensive immunosuppressive regimens, these patients who responded to ATG are long-term survivors with stable peripheral blood counts and a low rate of relapse.